The spectacle of feminism and machismo in two Peruvian cumbia singers: Marisol and Tony Rosado - Gutiérrez-Gómez, Edgar; Munaris-Parco, Sonia Beatriz (Frontiers in Sociology, 2023)
This research is based on the collection of information from the most important media in Peru, concentrated in two business owners: Grupo La República and Grupo El Comercio of journalistic domain in national information. These news media have sections of entertainment where the private lives of representative characters are exposed, such as the singers "Marisol, The Female Pharaoh of Cumbia" and "Tony Rosado, The Nightingale of Cumbia," from which the difference of extremist feminism tolerated in Marisol and the condemned machismo in Tony Rosado is popularized. This tolerance, hidden in the female voice, feeds machismo, justifies the mistreatment of the male and makes male complaint synonymous with cowardice.